Supplier Selection at Kerneos, Inc - Munson, Chuck; Li, Ling; Kosiek, Ted; Marsillac, Erika (Pearson, 2013)
This new supply chain management case study examines supplier selection at Kerneos, Incorporated, a leading manufacturer of cement products based on alumina content. It describes the critical role of supplier selection in Kerneos's supply chain transformation, which is using new IT tools to link distribution and sales demand more tightly with production planning and placing far greater emphasis on working capital. Focusing on realistic issues and challenges throughout, this case study offers exceptional value to both students and practitioners. Authors: Ling Li and Erika Marsillac, Old Dominion University; Ted Kosiek, Kerneos, Incorporated.
Online resource; Title from title page (viewed September 11, 2013)
Keywords: Business logistics; Business logistics -- Management; Logistique (Organisation); Logistique (Organisation); Gestion; Business logistics; Management